The comparative study between the conventional reits and islamic reits case study: starhill reit and axis-reit / Hafizatul Akmal Zainal Abidin - Zainal Abidin, Hafizatul Akmal (2010)
Real estate has been the important component of the institutional of investment portfolios over many years in Malaysia. Nowadays, real estate has been transformed into the combination of the trust fund. Real Estate Investment Trusts (REITs) and Islamic Real Estate Investment Trusts (l-REITs) have been redeveloped the property industry in order to enhance and encourage the economic and capital market in Malaysia. Furthermore, investors will look and find the opportunity to invest in such investment which will give better return not only for short term but also for long term period. Therefore, this comparative study is attempted to analyze the differences between the conventional REITs and Islamic REITs. The comparative study includes five chapters that comprise the background of the study, the literature review, and case study, the analysis of comparative study and lastly the recommendation and conclusion.